Women and War in the Balkans: A Comparative Review Essay. Issue 1 (1st March 2019) - Bucur, Maria
Abstract : Alin Ciupală, Bătălia lor: Femeile din România în Primul Război Mondial (Their batt le: Women in Romania during World War I), Iași: Polirom, 2017, 392 pp., 48 illustrations, RON 39.95 (paperback), ISBN: 978-9-73466-577-8. Jelena Batinić, Women and Yugoslav Partisans: A History of World War II Resistance, Cambridge: Cambridge University Press, 2015, 287 pp., 11 illustrations, GBP 24.99 (paperback), ISBN: 978-1-31611-862-7.